Cell-based high-content approach for SARS-CoV-2 neutralization identifies unique monoclonal antibodies and PI3K pathway inhibitors - Carly R. Cabel; Carly R. Cabel; Briana A. Guzman; Elaheh Alizadeh; Elaheh Alizadeh; Elaheh Alizadeh; Shuaizhi Li; Cameron Holberg; Chonlarat Wichaidit; Darren A. Cusanovich; Darren A. Cusanovich; Darren A. Cusanovich; et al. (Frontiers in Cell and Developmental Biology)
The sudden rise of the SARS-CoV-2 virus and the delay in development of effective therapeutics for mitigation made evident a need for ways to screen compounds that can block infection and prevent further pathogenesis and spread. However, identifying effective drugs that are efficacious against viral infection and replication with minimal toxicity for the patient can be difficult. Monoclonal antibodies were shown to be effective, but as the SARS-CoV-2 mutated, these antibodies became ineffective. Small-molecule antivirals were identified using pseudovirus constructs to recapitulate infection in nonhuman cells, such as Vero E6 cells. However, the impact was limited due to poor translation of these compounds in the clinical setting. This is partly due to the lack of similarity of screening platforms to the in vivo physiology of the patient and partly because drugs effective in vitro showed dose-limiting toxicities. In this study, we performed two high-throughput screens in human lung adenocarcinoma cells with authentic SARS-CoV-2 virus to identify both monoclonal antibodies that neutralize the virus and clinically useful kinase inhibitors to block the virus and prioritize minimal host toxicity. Using high-content imaging combined with single-cell and multidimensional analysis, we identified antibodies and kinase inhibitors that reduce viral infection without affecting the host. Our screening technique uncovered novel antibodies and overlooked kinase inhibitors (i.e., PIK3i, mTORi, and multiple RTKi) that could be effective against the SARS-CoV-2 virus. Further characterization of these molecules will streamline the repurposing of compounds for the treatment of future pandemics and uncover novel mechanisms viruses use to hijack and infect host cells.